Modul Inspirasi Kegiatan Kampus Merdeka Inbound 4 Universitas Mataram Untuk Peningkatan Kreativitas dan Inovasi: Modul Inspirasi Kegiatan Kampus Merdeka Inbound 4 Universitas Mataram Untuk Peningkatan Kreativitas dan Inovasi - Hasbi, Nurmi (Universitas Mataram, 2024)
The inspiration module activity is an activity to share information from resource persons who are experts in their fields and have been selected by the recipient campus. The inspiration module activity is 2 of 16 activities of the Merdeka Student Exchange Program. This diversity aims to increase students' knowledge and creativity obtained from resource persons who are experts in their fields. This inspiration activity is carried out by 1 lecturer of the Nusantara module, 2 resource persons, 1 liaison officer and 23 students participating in the Nusantara module. The inspiration activity was carried out in two activities. The two inspiration activities carried out were a Talk show with NTB art and tourism activists